Comparison between paracervical block and intrauterine lidocaine for pain management in surgical termination of first-trimester miscarriage: a randomized clinical trial - Doaa M. Effat; Mona A. Elkafrawy; Amira A.E. Shaban (Al-Azhar Assiut Medical Journal)
Background and aim Pain relief is a fundamental issue for women requiring gynecological procedures, including first-trimester evacuation. This study aimed to evaluate and compare the efficacy of paracervical block versus intrauterine lidocaine instillation versus combined paracervical block and intrauterine lidocaine anesthesia as pain-relief methods during surgical termination of first-trimester miscarriage on perceived pain, satisfaction, side effects, and safety. Patients and methods One hundred fifty pregnant women suffering from first-trimester miscarriage and requiring pregnancy termination were randomly assigned into three equal groups. Group I (n=50), receiving paracervical block (10 ml of 2% of lidocaine 100 mg). Group II (n=50), received (10 ml of 2% lidocaine intrauterine). Group III received both of paracervical block and intrauterine lidocaine. Assessment of pain was measured for participants by numeric rating scale three times, intraoperative, immediately, after, and 30 min postoperative. Results There was a significant decrease of pain-perception level in women of group III compared with group I and group II. There was an insignificant difference in the frequency of adverse effects of drug like nausea, vomiting, drowsiness, and dizziness among the study groups. In terms of pain-relief satisfaction, there was adequate satisfaction in group III compared with other groups. Conclusion Injection of 2% lidocaine intrauterine in combination with standard paracervical block significantly provides adequate intraoperative and postoperative pain relief and satisfaction more than paracervical block or intrauterine lidocaine alone in the first-trimester surgical miscarriage. Also, this method is safe and effective.